Smart Nanoformulation Based on Polymeric Magnetic Nanoparticles and Vincristine Drug: A Novel Therapy for Apoptotic Gene Expression in Tumors - Sharafaldin Al-Musawi; Sumayah Ibraheem; Salih Abdul Mahdi; Salim Albukhaty; Adawiya J. Haider; Afraa Ali Kadhim; Kadhim Ali Kadhim; Haitham Ali Kadhim; Hassan Al-Karagoly (Life, 2021)
Background: Advanced nanobiotechnology provides safe and efficient drug delivery systems to deliver chemotherapy that targets cancer cells efficiently. Methods: A polymeric-magnetic nanocarrier was composed of a dextran (DEX) shell, a superparamagnetic iron oxide (SPION) core and was conjugated with folate (FA) to carry the anticancer drug vincristine (VNC) in Tera-1 testicular tumor cells. The molecular mechanisms by which apoptosis was induced were analyzed using flow cytometry and qPCR, which exhibited anticancer activity of nanoparticles (NPs). Results: This nanocarrier revealed a controlled release of VNC in citrate and phosphate buffer solutions that were maintained at pH 5.5 and pH 7.4, respectively. The Inhibitory concentration (IC50) values were greater than 5 mg/mL and displayed ten times higher cytotoxicity than the comparable free drug concentration. The Caspase-9 and P53 expressions were increased, whereas P21 and AKt1 decreased noticeably in the treated cells. The results point to the possible activation of apoptosis following treatment with NPs loaded with vincristine.